Impacts of load distribution and lane width on pavement rutting performance for automated vehicles. Issue 12 (15th October 2022) - Yeganeh, Ali; Vandoren, Bram; Pirdavani, Ali
ABSTRACT: Over the recent years, considerable attention has been drawn to intelligent driving technologies and particularly to automated vehicles (AVs). The deployment of AVs would provide the opportunity to have more control over the dynamics of the vehicle, including its lateral movement, which can affect the pavement's long-term rutting performance. The controlled lateral movement of the AVs may also imply a reduced lane width. This paper evaluates the impacts of dedicating a reduced lane width to AVs on pavement rutting performance, considering two lateral movement modes for AVs; zero-wander and uniform-wander. A finite element model was developed using ABAQUS software. The rutting simulation results of this study showed that the abrupt changes in the loading schemes of the zero- and uniform-wander modes cause considerable accumulated rutting in the edges of the loading areas. This is significantly greater than the total rutting induced by the human-driven vehicles (HDVs) following the normal-wander mode, which causes a compensated rutting behaviour by a gradual increase in loading time. Furthermore, the comparison between rutting depths in different lane widths reveals that when dedicating the narrower lane for AVs with a uniform-wander distribution, the pavement's total rutting depth would remarkably increase compared to the wider lanes.